2015
DOI: 10.1080/09593330.2015.1042922
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of agro-industrial wastes, their state, and mixing ratio for maximum polygalacturonase and biomass production in submerged fermentation

Abstract: The potential of important agro-industrial wastes, apple pomace (AP) and orange peel (OP) as C sources, was investigated in the maximization of polygalacturonase (PG), an industrially significant enzyme, using an industrially important microorganism Aspergillus sojae. Factors such as various hydrolysis forms of the C sources (hydrolysed-AP, non-hydrolysed-AP, hydrolysed-AP + OP, non-hydrolysed-AP + OP) and N sources (ammonium sulphate and urea), and incubation time (4, 6, and 8 days) were screened. It was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Göğüş et al . 4 reported that apple pomace and orange peel may be used as culture media for the production of a polygalacturonase enzyme that serves as a pectolytic enzyme in the industrial production of wine and fruit juices.…”
Section: Introductionmentioning
confidence: 99%
“…Göğüş et al . 4 reported that apple pomace and orange peel may be used as culture media for the production of a polygalacturonase enzyme that serves as a pectolytic enzyme in the industrial production of wine and fruit juices.…”
Section: Introductionmentioning
confidence: 99%
“…All residues were dried overnight at 45 °C in hot air drying oven (0.4 ms-1), milled (propeller mill Arcano, 24000 rpm, 460W), passed through 35 mesh sieve to have uniform size particles of the material, and kept in air tight plastic containers for further analysis [28,29].…”
Section: Physicochemical Characterization Of Agro-industrial Residuesmentioning
confidence: 99%